2023
DOI: 10.1101/2023.01.16.524277
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A single amino acid polymorphism in natural Metchnikowin alleles ofDrosophilaresults in systemic immunity and life history tradeoffs

Abstract: Antimicrobial peptides (AMPs) are at the interface of interactions between hosts and microbes and are therefore expected to be fast evolving in a coevolutionary arms race with pathogens. In contrast, previous work demonstrated that one AMP, Metchikowin (Mtk), has a single residue that segregates as either proline (P) or arginine (R) in populations of four differentDrosophilaspecies, some of which diverged more than 10 million years ago. The recurrent finding of this polymorphism regardless of geography or host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…In Drosophila, AMP genes are transcriptionally regulated by the Toll and Imd nuclear factor-kB (NF-kB) signaling pathways (8). Recent work has shown that individual effectors can play prominent roles in the defense against specific pathogens (11)(12)(13)(14)(15)(16)(17)(18)(19). Consistent with this, population genetics studies have highlighted genetic variants in AMPs correlated with susceptibility against specific pathogens.…”
mentioning
confidence: 86%
“…In Drosophila, AMP genes are transcriptionally regulated by the Toll and Imd nuclear factor-kB (NF-kB) signaling pathways (8). Recent work has shown that individual effectors can play prominent roles in the defense against specific pathogens (11)(12)(13)(14)(15)(16)(17)(18)(19). Consistent with this, population genetics studies have highlighted genetic variants in AMPs correlated with susceptibility against specific pathogens.…”
mentioning
confidence: 86%
“… Badinloo et al (2018) found that chronic and ubiquitous AMP overexpression reduced fly lifespan alongside induction of mitochondrial stress. A recent study of the AMP gene Metchnikowin further suggests a trade-off between greater antimicrobial activity and host fitness ( Perlmutter et al, 2023 ). These results suggest AMPs could be deleterious to host fitness, which is also supported by evolutionary studies showing that AMP deletions segregate in wild populations ( Early et al, 2017 ; Hanson et al, 2019b ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, symbiotic microorganisms can enhance host resistance against pathogens and parasites by stimulating or priming the host's immune system (29). This mechanism has been suggested to mediate the host protection by Wolbachia against viruses and certain bacteria (18,30), and potentially against fungi (17). Some studies indicated that Spiroplasma may also induce immune responses in fruit flies, particularly the Toll pathway (19,31).…”
Section: Introductionmentioning
confidence: 99%
“…Some facultative endosymbionts also bring ecological advantages to their hosts, such as tolerance to heat (6) or protection against natural enemies (7)(8)(9), which also contributes to the maintenance and spread of defensive symbionts in insect populations (10)(11)(12). Symbiont-mediated defense has been confirmed in diverse insects, protecting them against a variety of antagonists, like RNA viruses, nematodes and parasitic wasps, and pathogenic fungi (9,10,(13)(14)(15)(16)(17)(18)(19). The fact that taxonomically different symbionts can provide protection against various parasites suggests that the defensive nature of insect-microbe symbiosis is a common, if not predominant, aspect of insect symbioses.…”
Section: Introductionmentioning
confidence: 99%